The influence of post-visit factors on multifaceted destination image formation - Jia, Xiong (2017)
Destination image, an important element for destination positioning and selection process, is a widely-studied topic in tourism for the last four decades. Despite the wide coverage given to this topic, there are still disputes related to the conceptualization of destination image construct and formation. First, there is a myriad of literature supporting the role of cognitive and affective images as the dualcomponents of destination image construct. But the literature pays little attention to conative image and seems silent on multisensory image. Responding to these limitations, this research attempted to incorporate the four image components and investigate their interrelationships. Second, studies on destination image formation tend to focus on the pre-visit phase while the factors in the post-visit phase are neglected. This research attempted to investigate the influence of previous experience, tourist experience and intensity of visit on post-visit destination image formation. Based on the setting of Phoenix ancient town in China, this research used a mixed-method approach to collect data from domestic tourists, and employed structural equation modeling and multi-group analysis to analyze the data. Finally, based on the data analysis, the research verified the interrelationships between cognitive, affective, conative and multisensory images and proved that previous experience, tourist experience and intensity of visit either positively or negatively influence different image components’ formation. The contribution of this research has added to the limited knowledge on China’s ancient town tourism. Practically, this research has managerial implications and would help destination marketers to identify, improve and promote the touristic destinations by creating a positive and unique destination image.